2019
DOI: 10.1371/journal.pone.0220917
|View full text |Cite
|
Sign up to set email alerts
|

Mouse TMCO5 is localized to the manchette microtubules involved in vesicle transfer in the elongating spermatids

Abstract: As a result of a high-throughput in situ hybridization screening for adult mouse testes, we found that the mRNA for Tmco5 is expressed in round and elongating spermatids. Tmco5 belongs to the Tmco ( Transmembrane and coiled-coil domains ) gene family and has a coiled-coil domain in the N-terminal and a transmembrane domain in the C-terminal region. A monoclonal antibody rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Previous studies in which testis-enriched genes were inactivated have successfully demonstrated the contributions of these genes to male infertility and the impairment of spermatogenesis in mice, underscoring their importance to reproductive outcomes. This approach has been used to evaluate many candidate testes-enriched genes to date, with many having been found to play detectable roles in the regulation of murine spermatogenesis ( Castaneda et al, 2017 ; Gao et al, 2020 ; Hua et al, 2019 ; Shah et al, 2021 ; Shibuya et al, 2015 ; Yamase et al, 2019 ; Yang et al, 2021 ; Zhang et al, 2019 ), whereas others are dispensable in this context, including FANK1 , Hspa1l , and Tex33 ( Wang et al, 2020 ; Zhang et al, 2019 ; Zhu et al, 2020 ). It has been suggested that the proteins encoded by these genes may have redundant functions in spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in which testis-enriched genes were inactivated have successfully demonstrated the contributions of these genes to male infertility and the impairment of spermatogenesis in mice, underscoring their importance to reproductive outcomes. This approach has been used to evaluate many candidate testes-enriched genes to date, with many having been found to play detectable roles in the regulation of murine spermatogenesis ( Castaneda et al, 2017 ; Gao et al, 2020 ; Hua et al, 2019 ; Shah et al, 2021 ; Shibuya et al, 2015 ; Yamase et al, 2019 ; Yang et al, 2021 ; Zhang et al, 2019 ), whereas others are dispensable in this context, including FANK1 , Hspa1l , and Tex33 ( Wang et al, 2020 ; Zhang et al, 2019 ; Zhu et al, 2020 ). It has been suggested that the proteins encoded by these genes may have redundant functions in spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to determine its interacting partners as well as the function this protein plays in the manchette. TMCO5A has been recently detected in the manchette [204]. However, its function in this organelle and the interacting proteins are still unknown.…”
Section: Intramanchette Transport Interactomementioning
confidence: 99%
“…However, its function in this organelle and the interacting proteins are still unknown. Because of localization in the Golgi, it has been suggested that TMCO5A may be involved in vesicle transport in the manchette [204], but this needs further experimental confirmations. As a whole, the proteins that failed to be incorporated into the interactome deserve further study in order to understand their roles in the manchette and to identify their interacting partners.…”
Section: Intramanchette Transport Interactomementioning
confidence: 99%